Coconut leaf nutrient levels of bearing dwarf varieties and physiological critical and adequacy levels in crop nutrition management - Severino S. Magat (International Coconut Community, 2003)
An analysis of the leaf nutrient concentrations data of bearing palms (grown in a suitable coastal ecosystem) of three coconut dwarf varieties [Malayan yellow dwarf(MLYD), Catigan green dwarf(CATGD) and Tacunan green dwarf(TACGD)] planted at the designed-genetic blocks of the Zamboanga Research Center, San Ramon, Zamboanga City (Western Mindanao, Philippines), covering the period 1995-1999, was conducted . The variability and trend of each leaf nutrient (N, P, K, Ca, Mg, Na, Cl, S and B) over the years was determined. The critical levels of leaf nutrients are estimated based on the average or normal values of the historical data. An initial general reference guide on the physiological leaf critical levels of dwarfs is presented, as follows (leaf #14, dry matter): 1.70% N: 0.125% P; 0.90% K; 0.38% Ca; 0.26% Mg; ; 0.12% Na, 0.37% Cl; 0.15% S; and 11 ppm B. The implications of knowing the adequacy and critical levels in leaves as an indicator of crop nutrition to optimize the yield potential of dwarf varieties of coconut are discussed.